To study clinical and cardiovascular profile including TMT changes in tobacco addicts - Sudhir Mourya; Ashok Thakur; Aastha Bansal; Amit Badole (International Journal of Medical Research and Review, 2014)
Introduction: Tobacco addiction remains a substantial problem in the worldwide. As a consequence of its addictive qualities, the consumption of tobacco often becomes a lifelong habit with cumulative and deleterious effects on health. The Treadmill test unmasks the occult disease and thereby influences the long term prognosis and treatment.Material methods: A population based prospective observational study was performed in 200 subjects who agreed to participate in the evaluation and had a history of isolated tobacco-chewing and smoking were enrolled in study. The prevalence of major coronary risk factors- obesity, truncal obesity, hypertension, fasting hyperglycemia, and lipid levels were estimated using current guidelines. Electrocardiogram, Chest radiography and treadmill stress test was done in subjects when indicated by symptoms.Results: Most of the subjects were in the age group of 41-50 years (87%), were male (96.5%). Maximum subjects were consuming tobacco for more than 20 years. Atypical chest pain was the most common associated symptom (48.5%). most of subjects were motivated by others either by peer groups or family members (25.5% and 22.5% respectively), Number of positive T.M.T. cases increases with age. In 41 to 50 year age group incidence of positive T.M.T. was more common (14.9%) and we found that the duration of addiction was more important than the quantity of tobacco.Conclusion: Tobacco is the single greatest cause of preventable death globally, The effects depend on the number of years and how much a person smokes and chews. Tobacco addiction is highly prevalent in this part of country. The present work has been performed with the idea to detect the role of tobacco addiction in the development of the coronary artery disease. The treadmill test is presently the most simple, least expensive and fairly sensitive, non-invasive screening test for the early detection of latent ischemic heart disease.